Trends in graphene reinforced polyamide nanocomposite for functional application: a review. Issue 9 (13th June 2019) - Kausar, Ayesha
ABSTRACT: This review outlines significant aspects and vital progression from polyamide – to – polyamide/graphene nanocomposite – to – technical application. Polyamide forms an important class of engineering thermoplastic polymers with exceptional mechanical, abrasion, wear, barrier, and crystallinity properties. Graphene is a unique nanocarbon having exclusive electrical, optical, mechanical, thermal, and chemical performance. Consequently, polyamide/graphene nanocomposite has revealed multifunctional properties and high performance owing to the synergistic effect of polymer and graphene. Here, interfacial interaction, dispersion in matrix, and processing technique used affect the final nanocomposite performance. A range of technological fields have been profited using polyamide/graphene nanocomposites including non-flammable materials, membranes, coatings, textile, and packaging industries. Graphical Abstract: